2015
DOI: 10.1016/j.neuroscience.2015.07.072
|View full text |Cite
|
Sign up to set email alerts
|

Children with cerebral palsy have uncharacteristic somatosensory cortical oscillations after stimulation of the hand mechanoreceptors

Abstract: Numerous clinical investigations have reported that children with cerebral palsy (CP) have tactile discrimination deficits that likely limit their ability to plan and manipulate objects. Despite this clinical awareness, we still have a substantial knowledge gap in our understanding of the neurological basis for these tactile discrimination deficits. Previously, we have shown that children with CP have aberrant alpha-theta (4–14 Hz) oscillations in the somatosensory cortices following tactile stimulation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 47 publications
3
35
0
Order By: Relevance
“…130 A related study of particular interest showed that theta-alpha synchronization in the somatosensory cortices was normal in children with CP following tactile stimulation of the hand. 131 Since the children in this study did not have upper extremity impairments, these findings may suggest that theta-alpha synchronization is selectively disturbed in CP and is only abnormal in neural regions that serve severely impaired limbs.…”
Section: Cerebral Palsy (Cp)mentioning
confidence: 71%
“…130 A related study of particular interest showed that theta-alpha synchronization in the somatosensory cortices was normal in children with CP following tactile stimulation of the hand. 131 Since the children in this study did not have upper extremity impairments, these findings may suggest that theta-alpha synchronization is selectively disturbed in CP and is only abnormal in neural regions that serve severely impaired limbs.…”
Section: Cerebral Palsy (Cp)mentioning
confidence: 71%
“…Using time-frequency analysis, we tested whether the reactivity of the ongoing S1 activity in children with HCP differs between the LA and MA hemisphere or in comparison with TD children. Very few studies have examined the sensorimotor oscillatory responses to tactile or electrical stimuli of the upper limbs in children with CP ( Guo et al, 2012 , Pihko et al, 2014 , Kurz et al, 2015a , Kurz et al, 2015b ). Except Guo et al (2012) , prior studies have focused their attention on lower frequency bands (i.e., alpha and beta), which are traditionally considered to be closely tied to the activation of sensory ( van Ede et al, 2011 ) and/or motor cortex ( Perry et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…These studies performed statistics either in the frequency or the time-frequency domain for predefined bands of interest (i.e. from 70 to 200 Hz for gamma in Guo et al, 2012 ; 6–14 Hz for alpha and 12–27 Hz for beta in Pihko et al, 2014 ; and 4–14 Hz for theta-alpha and 18–34 Hz for beta in Kurz et al, 2015a , Kurz et al, 2015b ). Here, we performed statistics in the entire spectrum from 1 to 100 Hz without a priori assumptions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We suspect that this developmental change will be partially linked with the maturation of the fiber tracts that serve the cortical areas identified in this investigation. Understanding this potential link is critical for advancing translational studies of the sensorimotor system in patients with developmental disabilities (e.g., Kurz et al 2014b, 2015a, b; Wilson et al 2016), and should be considered high priority for clinical studies of motor control.…”
Section: Discussionmentioning
confidence: 99%